Match situations leading to head injuries in professional male football (soccer) - A video-based analysis over 12 years - Beaudouin, F.; aus der Fünten, K.; Tröß, T.; Reinsberger, C.; Meyer, T. (Clinical Journal of Sport Medicine, 2020)
Objective: To identify risk situations promoting head injuries in professional male football (soccer) and to investigate the impact of a rule change in 2006 punishing elbow-head contacts. Design: Analysis of video sequences of head events leading to head injury. Participants: Professional football players of the first male German Bundesliga. Main Outcome Measures: Observational criteria of head impacts on video recordings (players' actions preceding head injuries, foul play—referee's decision and assessment of rater, ball possession, on-pitch medical treatment, and consequences of head impact). Results: Three hundred thirty-four head injuries were reported in kicker Sportmagazin corresponding to an incidence rate of 2.25 (95% confidence interval 2.01-2.51) per 1000 player match hours. The injured player predominantly jumped (60%), headed the ball (36%), or ran forwards (20%); the noninjured players mainly jumped (64%), headed the ball (27%), or raised the elbow to the head (23%). Free ball situations (2 players challenge for the ball) caused most of the head injuries (81%). The players' action "raising the elbow" during a head injury seemed to be lower after the rule change. Conclusions: Jumping for the ball with the intention of heading is the predominant action associated with head injury risk. Head injuries occur most often when players challenge for the ball in a header duel. As head injuries bear the potential risk of long-term health sequelae, the identification of situational circumstances is essential to develop preventative means in the future.